Study of The Overhung Rotor-Shaft Instability and Whirling Observation Using a High Speed Camera - Anjani, Nyoman
Applications of overhung rotor-shaft system are commonly used in chemical, mining, and material processing industries. Generally, the system is useful for fluid machineries such as mixer, centrifugal pump, fan, and propeller. A flexible overhung rotor-shaft system will have a large deflection at the end of its shaft (the rotor’s part), especially when the rotor is in unstable condition. The consequences of such condition, in many cases in the industries, may result in catastrophic failures. In addition, a large deflection at the end of the rotating rotor is difficult to detect using ordinary contact sensors. So that, the objective of this research is to conduct an analytical and numerical studies regarding the instability that occurred in overhung rotor-shaft system, and conduct whirling observation using a high speed camera. In this research, an analytical modeling is conducted to investigate the effect of instability to the overhung rotor-shaft system in synchronous condition. The result of the analytical modeling was being compared to the result of numerical modeling which applying finite element method using a software of Matlab 7.10. From both results of these modelings, the vibration response, length, and speed of the overhung rotor-shaft system in critical condition can be calculated easily for every length of the shaft. Based on the whirling observation using a high speed camera with a speed of 1000 frame per second, showed that the overhung rotor-shaft system has a forward-whirling mode. Beside that, when the resonance occurred, the orbit shape of a rotating rotor is a perfect circle. This result is identical to those of analytical and numerical modeling of the overhung rotor-shaft system in synchronous condition. In addition, the shaft with a certain length will be plastically deformed or bent, before the rotating speed of the shaft exceeds its critical speed, and the deflection of the shaft will increase as the consequences of the unstable condition that happened in the overhung rotor-shaft system.